(untitled) (Scientific journal of the Fergana State University, 2024)
This article shows preliminary results on the accilimatization of medicinal Sano – Cassia L species in the conditions of the Fergana region. This plant species is of particular importance with the medicinal character of Cassia angustifolia L and large plantations are now being established in the regions of the Fergana region.